Effects of melatonin treatment on milk traits, reproductive performance and immune response in Sarda dairy sheep. Issue 1 (1st January 2021) - Cosso, Giovanni; Mura, Maria Consuelo; Pulinas, Luisa; Curone, Giulio; Vigo, Daniele; Carcangiu, Vincenzo; Luridiana, Sebastiano
Abstract: In ruminants, the role of melatonin in the control of reproductive seasonality is well reported, but it is still little known about its action on milk traits and on the immune system. The aim of this study was to assess the effect of melatonin on milk yield and composition, somatic cell count (SCC), some cytokine blood concentration and reproductive resumption in sheep. One hundred lactating sheep were allocated to two groups (of 50 sheep each), M (treated with melatonin) and C (controls), and exposed to the rams for 50 d. Time period in days from ram introduction to lambing (TRIL) and litter size were recorded. Every 15 d, from 1 March to 30 April, the individual daily milk yield was registered and milk composition and SCC, were analysed. The levels of Interleukin 2 and 6 (IL-2 and 6) and tumour necrosis factor-alpha (Tnf-α) were evaluated every 15 d. The highest fertility rate ( p < .01) and the shortest TRIL ( p < .05) was recorded in M group. Milk yield and composition were similar between groups. The somatic cells decreased continuously in the treated ewes ( p < .01) and increased continuously in untreated ewes ( p < .05). IL-2 and IL-6 increased in M group, although no statistical differences were found between groups. Melatonin administration improved reproductive efficiency, did not affect milk yield and composition and decreased somatic cells. This last effect could help to maintain healthy mammary gland and encourage farmers to reduce the use of drugs against mastitis. Highlights: Melatonin is involved in different physiological processes, such as the control of reproductive seasonality, milk production and the immune response. Melatonin administration in Sarda sheep did not modify milk yield and composition, decreased SCC and advanced reproductive resumption in spring. Melatonin could be used to strengthen the sheep immune response in order to reduce the use of drugs for both therapeutic and preventive purposes against mastitis.